Construction of Nonsinusoidal Oscillation Waveform Function and Technological Parameters for Continuous Casting Mold - Chao Zhou; Xingzhong Zhang; Fang Wang; Subo Ren (Complexity)
Nonsinusoidal oscillation techniques can shorten the negative strip time and improve the slab surface quality in the process of steel continuous casting. But the acceleration of nonsinusoidal oscillation is higher than that of the sinusoidal oscillation. So it is easy to result in the impact for the mold movement. To solve this problem, a nonsinusoidal oscillation waveform function of mold was constructed, which had good dynamic characteristics. And the smaller acceleration can reduce the impact of the oscillator. By analyzing the parameters of oscillation technology, the calculation method of each oscillation technological parameter for seven section functions was presented and the multitechnological parameter curves were given. Based on the technological parameters of sinusoidal oscillation, a synchronous control model of nonsinusoidal oscillation was determined. The results show that the parameters can satisfy the limit value in theory, which can enhance the casting speed, surface quality of slab, and provide reference for further practice in industry.